2009
DOI: 10.1128/aem.01370-09
|View full text |Cite
|
Sign up to set email alerts
|

Novel Alkane Hydroxylase Gene ( alkB ) Diversity in Sediments Associated with Hydrocarbon Seeps in the Timor Sea, Australia

Abstract: Hydrocarbon seeps provide inputs of petroleum hydrocarbons to widespread areas of the Timor Sea. Alkanes constitute the largest proportion of chemical components found in crude oils, and therefore genes involved in the biodegradation of these compounds may act as bioindicators for this ecosystem's response to seepage. To assess alkane biodegradation potential, the diversity and distribution of alkane hydroxylase (alkB) genes in sediments of the Timor Sea were studied. Deduced AlkB protein sequences derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 43 publications
5
61
1
Order By: Relevance
“…Weighted UniFrac analysis indicates no significant difference between ϭϱ sediment samples MC 294 4662 0-2 cm and MC 294 4664 0-2 cm (P=0.164), but significant differences between sediment and coral floc samples are observed (P=<0.001). Despite the differences in the diversity of alkB OTUs between samples, the majority of sequences are aligned to known alkane oxidizers affiliated to γ-Proteobacteria that are able to transform petroleum-derived carbon into fresh biomass in marine sediments (Pearson et al, 2005, Wasmund et al, 2009, Wang et al, 2010. The alkB gene diversity in this study is consistent with that observed for other GoM sediments (Smith et al, 2013) as well as other cold seep sites in Australia (Wasmund et al, 2009).…”
Section: Presence and Diversity Of Functional Genes Involved In Oil Dsupporting
confidence: 86%
See 1 more Smart Citation
“…Weighted UniFrac analysis indicates no significant difference between ϭϱ sediment samples MC 294 4662 0-2 cm and MC 294 4664 0-2 cm (P=0.164), but significant differences between sediment and coral floc samples are observed (P=<0.001). Despite the differences in the diversity of alkB OTUs between samples, the majority of sequences are aligned to known alkane oxidizers affiliated to γ-Proteobacteria that are able to transform petroleum-derived carbon into fresh biomass in marine sediments (Pearson et al, 2005, Wasmund et al, 2009, Wang et al, 2010. The alkB gene diversity in this study is consistent with that observed for other GoM sediments (Smith et al, 2013) as well as other cold seep sites in Australia (Wasmund et al, 2009).…”
Section: Presence and Diversity Of Functional Genes Involved In Oil Dsupporting
confidence: 86%
“…AlkB or assA/bssA sequences were aligned to related sequences retrieved from BLAST searches and from described strains where full sequences were available, then manually edited as necessary using the package software ClustalX 2.1 (Larkin et al, 2007). Mothur software was used to cluster alkB or assA/bssA gene sequences into operational taxonomic units (OTUs) at a distance threshold of 0.2 (80% amino acid sequence similarity; as in Kuhn et al, 2009, Wasmund et al, 2009, Smith et al, 2013 and ϭϬ generate other alpha and beta diversity measurements. After sequence processing, a total of 103 alkB protein sequences were deduced from sediment sample MC 294 4662 0-2 cm (dereplicated to 13 OTUs at 80% amino acid sequence identity), 80 protein sequences from sediment sample MC 294 4664 0-2 cm (18 OTUs at 80% identity), and 73 protein sequences from the coral floc (14 OTUs at 80% identity).…”
Section: Functional Gene Sequencing: Construction and Analysis Of Alkmentioning
confidence: 99%
“…Kuhn and co-workers [5] found new alkB genes when contaminated and uncontaminated marine sediments in Admiralty Bay, King George Island, Antarctica were analyzed. Similar results were obtained for samples from the Timor Sea in Australia [12] and from chronically polluted, sub Antarctic coastal sediments [13].…”
Section: Introductionsupporting
confidence: 82%
“…The presence of alkB gene in the environment, act as bioindicator of the environment's recovering ability, since the alkanes constitute the largest proportion of hydrocarbons in crude oils. (Wasmund et al, 2009;Paisse et al, 2011). Regarding the absence of PAH-RHDa gene, a pair of specific primers used resulted in no amplification, an indication that the isolates grew in the presence of some of the available PAH using unknown catabolism pathways for these hydrocarbons.…”
Section: Hydrocarbonmentioning
confidence: 98%